Application of the narmax method to the modelling of the nonlinearity of dynamic loudspeakers - DOBRUCKI, A. B.; PRUCHNICKI, P. (Archives of Acoustics, 2001)
The application of the NARMAX method to the modelling of the nonlinearity of dynamic loudspeakers is described. The principle of creating a polynomial representation of a model, the problems stemming from a too large number of model coefficients and the method of optimizing the model are presented. The method was tested on data from actual loudspeaker measurements. Different models are compared as regards their accuracy depending on the modelling parameters. Finally, the model characteristics are compared with the results of loudspeaker measurements performed by classical methods.